The ontogenetic path of human dendritic cells - Amon, Lukas; Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Dudziak, Diana (Molecular Immunology, 2020)
Dendritic cells (DCs) orchestrate adaptive immune responses. In healthy individuals, DCs are drivers and fine-tuners of T cell responses directed against invading pathogens or cancer cells. In parallel, DCs control autoreactive T cells, thereby maintaining T cell tolerance. Under various disease conditions, a disruption of this delicate balance can lead to chronic infections, tumor evasion, or autoimmunity. While great efforts have been made to unravel the origin and development of this powerful cell type in mice, only little is known about the ontogeny of human DCs. Here, we summarize the current understanding of the developmental path of DCs from hematopoietic stem cells to fully functional DCs in their local tissue environment and provide a template for the identification of DCs across various tissues.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Conventional; DC; Human; Ontogeny; Progeny; Transcription factor